Aktifitas Zat Aktif Berbasis Tanaman Tradisional Indonesia Dalam Penyembuhan Luka - Nurfiah, Nurfiah; Tahir, Takdir; Yusuf, Saldy (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background:Â Wound healing is a series of complex events that are interrelated and depend on one another. Wound healing can be accelerated using traditional medicine. Traditional medicine is one of the efforts to overcome health problems that have been passed down from generation to generation, the use of traditional plants in Indonesia is part of national culture and has been widely used by people since centuries ago. Purpose: Information about traditional plants that can be used in wound healing. Method: Literature obtained based on scientific databases such as Science direct, and Google Scholar with current pharmacological evidence. Result: Traditional medicine has the activity as an antioxidant, anti-inflammatory, antibacterial in wound healing reported from various studies at this time. Therefore, their research can be introduced as something natural and can be used as a remedy for wound healing. Conclusion: Traditional plants can heal wounds through a mechanism.Â